The effect of neuromuscular re-education and oral motor exercises on adaptation and masticatory performance in complete denture wearers- a systematic review - Diya Shetty Ganesh; Shipha Hegde; R. Nirupama (Frontiers in Dental Medicine, 2026)
Purpose This systematic review aimed to evaluate the effect of neuromuscular re-education, oral motor exercises, or biofeedback compared to standard post-insertion care on objective masticatory function and patient-reported outcomes in completely edentulous adults receiving new conventional complete dentures. Methods A pre-piloted search protocol was developed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses – Protocol guidelines (PRSIMA-P) and registered in PROSPERO (CRD420251186130). A comprehensive electronic search was conducted across various databases. The selected studies were further evaluated using the Cochrane ROB 2 tool for randomized controlled trials (RCTs) and the ROBINS-I V2 tool for non-randomized studies. Results The initial search yielded 1,517 records from which a final set of 3 articles (2 RCTs and 1 clinical trial) were included. Quality assessment indicated that one RCT had “some concerns,” one RCT was “high risk,” and the clinical trial was at “critical risk” of bias. A sensitivity analysis suggested that excluding the higher-risk studies did not alter the overall positive direction of the findings. The findings of the included studies indicated that oral motor exercises and biofeedback significantly improved the functional adaptation as well as patient satisfaction. Conclusion The presented evidence suggests that active neuromuscular training is a cost-effective and feasible intervention to improve the functional adaptation to conventional complete dentures. Further high-quality research is recommended to substantiate these findings and to develop a protocol advocating for oral motor exercises and biofeedback to be included as a part of post-insertion instructions for conventional complete dentures. Systematic Review Registration PROSPERO(CRD420251186130).